2021
DOI: 10.1007/s12633-021-01423-7
|View full text |Cite|
|
Sign up to set email alerts
|

Investigation into MoTe2 Based Dielectric Modulated AMFET Biosensor for Label-Free Detection of DNA Including Electric Variational Effects

Abstract: Due to limitations of Silicon, Transition metal dichalcogenides (TMD) based biosensors are popular in the recent times. In TMD family, Molybdenum telluride (MoTe2) is being studied a lot for different biosensing application. However, for DNA detection using TMD based DMFET, the effect of the electrical variations in DNA has not been studied before. Also, the impact of DNA-Electrode interaction on transducer level of DMFET is yet to be studied. In this article, we have proposed a Molybdenum telluride (MoTe2) ba… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…However, due to low-Fermilevel pinning and moderate band gap, molybdenum ditelluride (α-MoTe 2 )-based devices have received significant scientific attention for electronic and optoelectronics applications. Particularly, in recent research projects related to biosensor applications, molybdenum ditelluride (MoTe 2 ) has been utilized for DNA detection 23 and glucose detection. 24 Here, a few layers of thin MoTe 2 flakes were used to fabricate 2D-FET biosensors for the detection of the streptavidin protein.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, due to low-Fermilevel pinning and moderate band gap, molybdenum ditelluride (α-MoTe 2 )-based devices have received significant scientific attention for electronic and optoelectronics applications. Particularly, in recent research projects related to biosensor applications, molybdenum ditelluride (MoTe 2 ) has been utilized for DNA detection 23 and glucose detection. 24 Here, a few layers of thin MoTe 2 flakes were used to fabricate 2D-FET biosensors for the detection of the streptavidin protein.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Extensive research has been conducted to improve this limit by suitably choosing: (a) an advanced device structure, (b) channel material, (c) topology, and (d) biasing conditions. Architectures like silicon on insulator (SOI) dual gate FET [18], floating gate [19], SOI FET [20], junctionless FET [21], negative capacitance [22], tunnel FET [23], trench gate [24] and others [25][26][27] have been proposed to achieve a higher sensitivity. Among these, junctionless ISFET (n-n-n or p-p-p) has attracted much attention because of their low thermal budget and manufacturing simplicity by avoiding source-channel-drain abrupt junctions [20,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that MoTe 2 is the sole TMD material that has a silicon-like bandgap and can be grown in semiconducting (2 H) as well as metallic (1 T ′ ) phases [34]. Moreover, MoTe 2 -based devices offer low thermal conductivity and lower subthreshold swing (SS) with a high on/off current ratio [21]. As a sensor, MoTe 2 devices exhibited high sensitivity with a significantly improved recovery rate as reported by Feng et al [35].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, there are two main optical ways for sensing goals. The first method is fluorescence detection, and the second is label-free detection [5][6][7]. Label-free detection is one of the cheapest and easiest methods based on Photonic sensors containing dielectric materials providing precise responses with a high-quality (Q) factor output transmittance spectrum.…”
mentioning
confidence: 99%